Scientometrics in a changing research landscape - Bornmann, Lutz; Leydesdorff, Loet (EMBO reports, 2014)
Bibliometrics has become an integral component of quality assessment for science and funding decisions. The next challenge for scientometrics is to develop similarly reliable indicators for the social impact of research.